The whiskey rebels : a novel - Liss, David, 1966- (Brilliance Audio on compact disc., 2008)
A gripping novel of a conspiracy that threatens to topple the fledgling banking system of the post-Revolutionary War United States, featuring the unforgettable characters of Ethan Saunders and Joan Maycott, with Thomas Jefferson and Alexander Hamilton in secondary roles.